1983
DOI: 10.1007/bf00484443
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit linkage group VIII: The alleles of the prt gene

Abstract: The prt gene which is linked to the rabbit immunoglobulin kappa-light chain gene, ab, has two phenotypes, PRT+ and PRT-. These phenotypes can be distinguished only when serum proteins from different rabbits are separated by polyacrylamide gel electrophoresis. The serum protein profiles for PRT+ rabbits show a band that is located on the anodal side of transferrin. This band is missing in the serum profiles of PRT- rabbits. However, the PRT protein is present in these rabbits. An antiserum which reacts with PRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Genetic polymorphism of rabbit plasma pretransferrin (Prt) has previously been reported. This protein has a mobility slightly more anodal to transferrin in alkaline polyacrylamide gel electrophoresis and it is clearly visible by using a general-protein stain (Usher et al 1978(Usher et al , 1983Juneja et al 1984). In the above studies, three codominant Prt alleles were reported.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Genetic polymorphism of rabbit plasma pretransferrin (Prt) has previously been reported. This protein has a mobility slightly more anodal to transferrin in alkaline polyacrylamide gel electrophoresis and it is clearly visible by using a general-protein stain (Usher et al 1978(Usher et al , 1983Juneja et al 1984). In the above studies, three codominant Prt alleles were reported.…”
mentioning
confidence: 94%
“…A-B 3.5mrn; A-C 5.0mm; A-D 8.5mm; A-E 104Ornm; and A-F 15 The Prt protein, by virtue of its high degree of polymorphism and easy phenotyping method, is thus a useful genetic marker for studying breed relationships and linkage relations in rabbit. The Prt gene has previously been assigned to linkage group VIII of rabbits (Usher et al 1983). The isolation and characterization of rabbit Prt protein was recently reported by Usher et al (1984).…”
mentioning
confidence: 94%
See 1 more Smart Citation